ANALISA BIODIESEL MINYAK KELAPA SEBAGAI BAHAN BAKAR ALTERNATIF MINYAK DIESEL - Seno Darmanto; Ireng Sigit A (TRAKSI, 2006)
Research is done to analyze biodiesel of coconut oil as fuel of diesel engine. The analyzing is focused on properties potential of biodiesel of coconut oil as fuel of diesel engine. The research is done in laboratory with making biodiesel of coconut oil and testing properties of biodiesel. The testing of biodiesel consists of B5, B10, B15, B20, B25 and pure biodiesel of coconut oil. Based on analyzing data, it shows that biodiesel has flash point lower than diesel fuel. Biodiesel also has kinematics viscosity higher than diesel fuel. And specific gravity of biodiesel is higher than specific gravity of diesel fuel. Key word: coconut oil, biodiesel, properties, viscosity, flash point, specific gravity, heat value, cetane number